Load current balancing for 4-wire systems using harmonic treated TCR based SVCs - Abdulkareem Mokif Obais; Ali Abdulkareem Mukheef (Institute of Advanced Engineering and Science, 2022)
In this paper, a harmonic-treated thyristor-controlled reactor TCR is presented as a linearized harmonic-free compensating susceptance controllable in inductive and capacitive modes. The harmonic-treated TCR is a traditional TCR conditioned in such a manner that it can respond continuously and linearly to capacitive and inductive reactive current demands without noticeable harmonic association or active power contribution. The conditioned configuration is produced by equipping the TCR with self-harmonic suppressing and filtering circuitries, which guarantee harmonic cancellation with minimal no load operating losses. The harmonic treated TCR avoids the need to high power harmonic filters required to treat the harmonics of the traditional TCR. The devised susceptances are used to build a load current balancing system for grounded loads in a 380-V, 50Hz power distribution system. Both the compensating susceptances and the load current balancing system were designed and tested on PSpice. The simulation results have demonstrated the linearity, control continuity, and harmonic cancellation of the proposed harmonic-treated TCR as a fast response compensating susceptance reliable for load current balancing purposes. The proposed load current balancing system revealed superior treatment to various unbalance conditions, thus it is deservedly promoted to have the feasibility of supporting grids having fast varying loads.